Panorama da STEM Literacy nas pesquisas de Educação STEM - Melo, Graciele Carvalho de (2022)
STEM Education over the last 20 years has gained space in scholar environments all over the world, due to the importance the areas which compose its acronym, Science, Technology, Engineering and Mathematics, have to contemporary society, including Brazil, albeit timidly. Among the objectives of STEM Education, authors as Zollman (2012), Bybee (2013), Li et al. (2019) and Leung (2020) highlight the STEM Literacy as its core, and for this reason, comprehending it becomes essential for changes to be made in favor of STEM Education, mainly because both terms are codependent, it means, are influenced by each other. So, in this research were studied the thematics which substantiate the STEM Education and STEM Literacy, as well as the dynamic between the two terms, as means to observe the landscape of STEM Literacy in the Brazilian context based on the national research about the thematic. Therefore, this study corresponds to an applied research, of qualitative nature and descriptive-exploratory character, organized in three phases, namely: (1) execution of an analyzes about STEM Literacy on the world stage, from materials made available by the CAPES` Portal of Journals and BDTD, to comprehend how this term is presented to Brazilian researchers; (2) evaluation of the premises of STEM literacy on national productions about STEM Education, by means of the available publications on the CAPES` Portal of Journals and on BDTD, to comprehend how our researchers interpret this approach and; (3) investigation of the objectives and projections for STEM Literacy from the studies delimited by research groups registered on the CNPq directory. The results obtained on this research show that in the world scenery there is no consensus about the conceptualization of STEM Literacy and that its core is grounded on the subjects (students, teachers) involved in the teaching and learning process. It is also verified that STEM Literacy longs for the democratization and equity of STEM Education, valuing, besides the conceptual aspects, the procedural and attitudinal aspects related to the themes and problems which pervade the STEM Education. To meet this goal, it is necessary cognitive, psychomotor and affective-emotional domain about the situations addressed by the STEM areas, standing out the essentiality of problem resolution, investigation, hypothesis formulation and testing of said hypothesis for the construction of knowledge in STEM areas, development of competences and abilities, as well as the 4Cs (critical thinking, collaboration, communication and creativity), which are listed as paramount to every citizen on the 21st century. Furthermore, it was clear how the different existing concepts influenced the developed research. About the Brazilian reality, the publications revealed that Brazil still has a long way to go through when it comes to the research about STEM Education, since there are no studies focusing on comprehending STEM Literacy, even though signs of this term are seen on studies and in the present educational public politics themselves, which regulates the national education system.